Reproductive mananagement in buffalo herds - Campos-Jiménez, David (2022)
Buffalo production has increased mainly over the past years, more farmers have been dedicated to the production system of this species in Latin America. The objective of this review is to compile scientific literature corresponding to reproductive management and biotechnologies available for Bubalus bubalis bulls and cows. The information was gathered from books and scientific articles from academic databases and Google Scholar in a span of 5 months (March-July). Reproductive management of cows, bulls and biotechnologies applied to the species were covered. It was determined that productive efficiency of buffalos is strongly related to nutritional, reproductive, and animal welfare management, as well as environmental factors were this species develops. Improvements in biotechnologies applied to the buffalo reproduction were evince.